2020
DOI: 10.3390/jmse8060466
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Work Accident in Container Terminals Using the Fault Tree Analysis Method

Abstract: The use of containers in the world is increasing every year in line with international trade flows. In very complex container terminal operations, the risk of work accidents is inevitable and can happen at any time. Therefore, this paper aimed to identify accidents and potential risks occurring in the container terminals. For the case study, the analysis was used the data of accidents during five years in one of the major container terminals in Indonesia. Risk assessment is carried out using the risk matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
0
26
0
4
Order By: Relevance
“…The change in i(τ), ∆i, which can be attributed to the splitting and transmission of the samples to two subnodes τ l and τ r (with sample fractions p l = n l n and p r = n r n , respectively) based on a threshold t θ for variable θ, can be calculated using Equation (4).…”
Section: Random Forest Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in i(τ), ∆i, which can be attributed to the splitting and transmission of the samples to two subnodes τ l and τ r (with sample fractions p l = n l n and p r = n r n , respectively) based on a threshold t θ for variable θ, can be calculated using Equation (4).…”
Section: Random Forest Modelmentioning
confidence: 99%
“…Most of the existing studies on the risk assessment of maritime ports have focused on port security [1][2][3] and port safety [4][5][6]. Notably, most studies focusing on the security considered only unusual events such as hostile attacks [7] and the smuggling of weapons [8], and most studies pertaining to port safety focused on accidents that occurred during usual port activities such as loading, discharging, importing, and exporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTA method is used in a research study [11] for the risk assessment of the container terminal operations. The results have shown that human factors were the most common cause of accidents due to negligence in operating with equipment or vehicles.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Identifikasi bahaya dilakukan dengan metode observasi atau pengamatan langsung di tempat kerja dan diskusi/wawancara dengan tenaga kerja. Sedangkan penilaian risiko adalah usaha untuk mengkalkulasi besarnya suatu risiko agar dapat diketahui apakah risiko dapat diterima ataupun tidak dengan terlebih dahulu menganalisis tingkat kemungkinan terjadinya kecelakaan serta tingkat keparahan yang ditimbulkan [11] [12]. Determining control atau pengendalian risiko adalah suatu proses evaluasi terhadap meminimalkan potensi terjadinya bahaya pada setiap kegiatan kerja berdasarkan mesin dilakukan dengan mengevaluasi minimasi potensi bahaya pada setiap aktivitas pekerjaan berdasarkan mesin.…”
Section: Informasi Artikel Abstrakunclassified